Food Web Connectivity in a Mangrove–Seagrass–Patch Reef (MSP) Seascape: Lessons from a Tropical Back-Reef in Puerto Rico - Antonietta Quigg; R. J. David Wells; Jay R. Rooker; Ronald L. Hill; Larissa L. Kitchens; Michael A. Dance; David L. Moulton; Phillip J. Sanchez; Beatrice Padovani Ferreira (Fishes, 2023)
Alterations to the functions and connectivity of mangrove–seagrass–patch reef (MSP) seascapes have the potential to impact the survival, foraging activities, and movement of reef-dependent invertebrates (e.g., crabs and shrimp) and fishes. In the current study, we examined carbon flow in the Guánica Biosphere Reserve in southwestern Puerto Rico using pigment analysis of particulate organic matter and stable isotope analysis of carbon (δ13C) and nitrogen (δ15N) in flora and fauna. Several lines of evidence pointed to N2 fixers (cyanobacteria) being important for fueling primary productivity in this oligotrophic ecosystem including low (